Whisker / fiber modified light high-entropy alloy nano composite material and preparation method thereof

By introducing hybrid whiskers and fibers into lightweight high-entropy alloys and preparing them by vacuum arc smelting, the problems of decreasing strength and insufficient toughness in high-temperature environments are solved, and significant improvement in mechanical properties are achieved.

CN119899987APending Publication Date: 2025-04-29GUILIN UNIV OF AEROSPACE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411997163.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional lightweight high-entropy alloys may face problems such as decreased strength and insufficient toughness in high temperature environments.

Method used

By introducing hybrid whiskers and fibers for toughening and preparing by vacuum arc smelting, lightweight high-entropy alloy nanocomposites with excellent high temperature resistance were prepared.

Benefits of technology

It significantly improves the mechanical properties of lightweight high-entropy alloys, such as strength, toughness, high temperature resistance, corrosion resistance and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899987A_ABST
    Figure CN119899987A_ABST
Patent Text Reader

Abstract

The invention provides a whisker / fiber modified light high-entropy alloy nano composite material and a preparation method thereof, and relates to the technical field of light high-entropy alloy materials. The whisker / fiber modified light high-entropy alloy nano composite material comprises a light high-entropy alloy matrix and a hybrid whisker / fiber material, and based on the total weight of the composite material, the mass percentage of the hybrid whisker / fiber material is 0.01 wt.%-8.00 wt.%. According to the light high-entropy alloy nano composite material, the crystal whiskers and the fibers are added to serve as reinforcing and toughening materials, the lattice distortion effect, the hysteresis diffusion effect and the like of the light high-entropy alloy are enhanced, meanwhile, active elements contained in the crystal whiskers and the fibers can be internally adsorbed to grain boundaries, and the grain boundary strengthening and grain boundary pinning effects are formed; and the mechanical properties such as strength, hardness, high temperature resistance, corrosion resistance and wear resistance of the lightweight high-entropy alloy can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lightweight high entropy alloy materials, and in particular to a whisker / fiber modified lightweight high entropy alloy nanocomposite material and a preparation method thereof. Background Art

[0002] As a special type of alloy material, high-strength, high-toughness and lightweight high-entropy alloys have excellent comprehensive properties and are therefore receiving increasing attention. In 2004, Ye Junwei et al. and Cantor et al. proposed the concept of lightweight high-entropy alloys (HEAs) that are different from the traditional alloy design concept. Lightweight high-entropy alloys are alloys composed of 5 or more metal elements mixed in equal or approximately equal proportions. They have a low density and the content of each element is between 5% and 35% (molar fraction). Compared with traditional alloys with one main element, the unique composition of lightweight high-entropy alloys gives them excellent properties, such as high strength, high hardness, high wear resistance, high fracture toughness, excellent low-temperature performance and structural stability, and good corrosion resistance. Due to the large number of elements in the alloy and similar contents, the mixing entropy of the entire system is high, which is the origin of the name of lightweight high-entropy alloys. Despite the large number of elements, lightweight high-entropy alloys often have simple crystal structures, such as face-centered cubic (FCC) or body-centered cubic (BCC) solid solutions. Lightweight high entropy alloys with a single-phase FCC structure have good plasticity but low strength, while light high entropy alloys with a single-phase BCC structure have high strength but poor ductility. Therefore, it is often difficult for single-phase solid solution light high entropy alloys to achieve a balance between strength and plasticity. At the same time, when light high entropy alloys contain strong carbide-forming elements (such as Cr), these elements react with carbon to form coarse carbides, which may act as crack sources or stress concentration points in the alloy, thereby reducing the plasticity of the alloy. In addition, grain size and morphology also have a significant effect on the plasticity of the alloy. Fine grains are usually beneficial to improving the strength and plasticity of the alloy, but excessively large grains or irregular grain morphology may reduce the plasticity of the alloy. In terms of structural materials, light high entropy alloy nanomaterials can be used to prepare structural materials with high strength, high toughness and corrosion resistance, such as parts in the fields of aerospace, automobile manufacturing, and shipbuilding.

[0003] However, traditional lightweight high-entropy alloys may face problems such as reduced strength and insufficient toughness in high-temperature environments. Therefore, the development of lightweight high-entropy alloys with excellent performance has become a common goal pursued by industry players. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a whisker / fiber modified lightweight high entropy alloy nanocomposite material and a preparation method thereof, so as to solve at least one of the following existing problems: improving the strength of lightweight high entropy alloy materials and improving the toughness of lightweight high entropy alloy materials.

[0005] The purpose of the present invention is mainly achieved through the following technical solutions:

[0006] In the first aspect, the present invention provides a whisker / fiber modified lightweight high entropy alloy nanocomposite material, comprising a lightweight high entropy alloy matrix and a hybrid whisker / fiber material. Based on the total weight of the composite material, the mass percentage of the hybrid whisker / fiber material is 0.01wt.%-8.00wt.%.

[0007] Preferably, the hybrid whisker / fiber material comprises a whisker material and a fiber material, and the mass ratio of the whisker material to the fiber material is (0.01-1):1.

[0008] Preferably, the whisker material has a length of 1-70 μm and a diameter of 0.01-0.9 μm.

[0009] Preferably, the fiber material has a diameter of 0.1-1 μm and a length of 0.2 mm-150 mm.

[0010] Preferably, the material of the whisker material includes at least one of SiC, mullite, potassium titanate, aluminum borate, calcium sulfate, calcium carbonate, aluminum oxide, and zinc oxide.

[0011] Preferably, the fiber material is made of at least one of graphene-based carbon fiber, S-glass fiber, M-glass fiber, basalt fiber, quartz glass fiber, alumina fiber, and silicon nitride fiber.

[0012] Preferably, the lightweight high-entropy alloy matrix includes metal components, and the metal components include at least five of Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Hf, Ta, and W.

[0013] Preferably, the metal component includes a first metal component, a second metal component, a third metal component, a fourth metal component, and a fifth metal component, which are different from each other. Taking the total atomic percentage of the lightweight high entropy alloy matrix as 100%, the atomic percentages of the first metal component, the second metal component, the third metal component, the fourth metal component, and the fifth metal component are the same or different, and are each independently 5 to 35 at.%.

[0014] In a second aspect, the present invention provides a method for preparing the whisker / fiber modified lightweight high entropy alloy nanocomposite material, comprising:

[0015] A mixture including metal component powders is obtained, subjected to a first vacuum arc melting, and then whisker materials and fiber materials are added and subjected to a second vacuum arc melting to obtain the whisker / fiber modified lightweight high entropy alloy nanocomposite material.

[0016] Preferably, the temperature of the first vacuum arc melting is 2500-3000° C., and the pressure of the first vacuum arc melting is 0.05-0.08 Pa.

[0017] Preferably, the temperature of the second vacuum arc melting is 1500-1700° C., and the pressure of the second vacuum arc melting is 0.05-0.08 Pa.

[0018] In a third aspect, the present invention provides an application of the lightweight high entropy alloy nanocomposite material, wherein the lightweight high entropy alloy nanocomposite material is used for parts in the fields of aerospace, medicine, energy, military and transportation.

[0019] Beneficial effects:

[0020] The lightweight high entropy alloy nanocomposite material provided by the present invention has an enhancing effect on the lattice distortion effect, hysteresis diffusion effect, etc. of the lightweight high entropy alloy by adding whiskers and fibers as reinforcing and toughening materials. At the same time, the active elements contained in the whiskers and fibers can be internally adsorbed on the grain boundaries to form grain boundary strengthening and grain boundary pinning effects, which can refine the grains. This can not only improve the strength, hardness, and toughness of the lightweight high entropy alloy, but also help to improve the mechanical properties of the lightweight high entropy alloy, such as high temperature resistance, corrosion resistance, and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are SEM images of the graphene-based carbon fibers and mullite whiskers of Example 1 provided by the present invention, wherein (a) is a SEM image of the graphene-based carbon fibers, and (b) is a SEM image of the mullite whiskers.

[0022] Figure 2 These are SEM images of the materials of Comparative Example 1 and Example 1 provided by the present invention, wherein (a) is the SEM image of Comparative Example 1, and (b) is the SEM image of Example 1.

[0023] Figure 3 These are stress-strain curves of the materials of Example 1 and Comparative Example 1 provided by the present invention.

[0024] Figure 4 XRD curves of the materials of Example 1 and Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION

[0025] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.

[0026] Traditional lightweight high-entropy alloys may face problems such as decreased strength and insufficient toughness in high-temperature environments. In order to overcome these challenges, the present invention proposes to introduce hybrid whiskers and fibers for toughening and adopt vacuum arc melting method to prepare lightweight high-entropy alloy nanocomposites with excellent high-temperature resistance.

[0027] Hereinafter, the present invention will be described in detail.

[0028] In the first aspect, the present invention provides a whisker / fiber modified lightweight high entropy alloy nanocomposite material, comprising a lightweight high entropy alloy matrix and a hybrid whisker / fiber material. Based on the total weight of the composite material, the mass percentage of the hybrid whisker / fiber material is 0.01wt.%-8.00wt.%, for example, 0.01wt.%, 0.05wt.%, 0.1wt.%, 0.2wt.%, 0.3wt.%, 0.4wt.%, 0.5wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, 5.5wt.%, 6wt.%, 6.5wt.%, 7wt.%, 7.5wt.%, 8wt.%, etc., preferably 0.5wt.%-5wt.%.

[0029] In the present invention, the hybrid whisker / fiber material is hybridized by whiskers and fibers to increase the toughness and strength of the composite material. In some specific embodiments of the present invention, the hybrid whisker / fiber material includes nano whisker material and nano fiber material. Preferably, in the hybrid whisker / fiber material, the mass ratio of nano whisker material to nano fiber material is (0.01-1):1, for example, 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc., preferably (0.2-1):1.

[0030] In some specific embodiments of the present invention, the length of the nano whisker material is between 1-70 μm and the diameter is between 0.01-0.9 μm.

[0031] In some specific embodiments of the present invention, the nanowhisker material includes one or more of SiC, mullite, potassium titanate, aluminum borate, calcium sulfate, calcium carbonate, aluminum oxide, zinc oxide, etc., preferably at least one of mullite, SiC, potassium titanate, aluminum borate, aluminum oxide, zinc oxide.

[0032] In some specific embodiments of the present invention, the diameter of the nanofiber material is between 0.1-1 μm, and the length is between 0.2 mm-150 mm.

[0033] In some specific embodiments of the present invention, the type of nanofiber material is one or more of graphene-based carbon fiber, S-glass fiber (borosilicate fiber), M-glass fiber (magnesium aluminum silicate fiber), basalt fiber, quartz glass fiber, alumina fiber, silicon nitride fiber, etc., preferably at least one of graphene-based carbon fiber, S-glass fiber, quartz glass fiber, alumina fiber, silicon nitride fiber, and M-glass fiber.

[0034] In some specific embodiments of the present invention, the lightweight high entropy alloy matrix includes five or more metal components. Preferably, the types of metal components are at least five of Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Hf, Ta, and W.

[0035] In some specific embodiments of the present invention, the light high entropy alloy matrix includes a first metal component, a second metal component, a third metal component, a fourth metal component, and a fifth metal component. The total atomic percentage of the light high entropy alloy matrix is ​​100%, and the atomic percentages of the first metal component, the second metal component, the third metal component, the fourth metal component, and the fifth metal component are the same or different, and are independently 5 to 35 at.%, such as 5 at.%, 8 at.%, 11 at.%, 14 at.%, 17 at.%, 20 at.%, 23 at.%, 26 at.%, 29 at.%, 32 at.%, 35 at.%, etc., and the total atomic percentage is 100%. .

[0036] In some specific embodiments of the present invention, the lightweight high entropy alloy material refers to an alloy material having an alloy density not greater than the iron density of 7.87 g / cm3, preferably 3.5-7.87 g / cm3, and a configuration entropy greater than 1.5R under random atomic occupancy.

[0037] The light high entropy alloy nanocomposite material provided by the present invention is an alloy made of five or more metals in equal or approximately equal amounts, wherein nano hybrid whiskers / fibers are added as reinforcing and toughening materials, which have an enhancing effect on the lattice distortion effect, hysteresis diffusion effect, etc. of the light high entropy alloy, and at the same time, the active elements contained in the nano hybrid whiskers / fibers can be internally adsorbed on the grain boundaries to form grain boundary strengthening and grain boundary pinning effects, which can refine the grains and improve the strength, hardness, high temperature resistance, corrosion resistance, wear resistance and other mechanical properties of the light high entropy alloy. The nanocomposite material prepared by combining nano hybrid whiskers / fibers with light high entropy alloys further improves the performance of light high entropy alloys and can be widely used in aerospace, medicine, energy, transportation and other fields.

[0038] In the present invention, the nano hybrid whisker / fiber material has a significant strengthening and toughening effect on the lightweight high entropy alloy material, and the outstanding advantages are as follows:

[0039] (1) Nano hybrid whiskers / fibers are a kind of long fiber-short whisker-like materials with high orientation. The introduction of whiskers and fibers can optimize the microscopic and macroscopic structures of composite materials. Its diameter is very small, reaching the order of micrometers, and does not contain defects existing in ordinary materials, such as grain boundaries, dislocations, holes, etc. Its atomic arrangement is highly ordered, so its strength is close to the theoretical value of a complete crystal. Its mechanical strength is equal to the force between adjacent atoms. The highly oriented structure of hybrid whiskers / fibers not only makes it have high strength, high modulus and high elongation, but the strength of nano hybrid whiskers / fibers is much higher than that of other single short fibers. Therefore, the present invention is mainly used as a reinforcement for lightweight high entropy alloy materials and is used to manufacture lightweight high entropy alloy composite materials. Compared with traditional single crystal nano whiskers or nanofibers, nano hybrid whiskers / fibers are usually formed by combining two or more materials of different scales and properties. This combination can produce a synergistic effect between single crystal nano whiskers and nanofibers, forming a long-scale and short-scale mutual compensation effect, mainly a synergistic toughening effect. Whiskers and fibers can also produce a synergistic toughening effect in lightweight high entropy alloy nanocomposites. When external force acts on the composite material, whiskers and fibers can absorb energy together and delay the fracture process, thereby improving the overall toughness of the composite material. In summary, the mechanism of hybrid whisker fiber toughening lightweight high entropy alloy nanocomposites involves multiple aspects such as the toughening mechanism of whiskers and fibers, the characteristics of lightweight high entropy alloys, and the optimization of the microstructure of the composite material. The combined effect of these mechanisms makes the hybrid whisker / fiber toughened lightweight high entropy alloy nanocomposites have excellent physical and chemical properties. Hybrid whiskers / fibers are superior to single crystal whiskers in mechanical properties, such as strength, toughness, hardness, etc. Hybrid whiskers / fibers, due to their combination of properties of multiple materials, may have multiple properties such as electrical conductivity, thermal conductivity, and magnetism. They can not only strengthen and toughen lightweight high-entropy alloy materials, but also improve the comprehensive performance of nanocomposites to a certain extent. From the perspective of processing technology, hybrid whiskers / fibers have better processing performance. Different materials in hybrid whiskers / fibers may have different melting points and fluidity, making it easier to achieve precise control of shape and size during processing.

[0040] (2) The whiskers in the nano hybrid whisker / fiber materials added to the lightweight high entropy alloy are single crystal nanomaterials. Whiskers are a nanoscale material grown from high-purity single crystals and have the characteristics of high strength, high modulus and high elongation. Whiskers have a good single crystal structure and a regular and orderly lattice arrangement. During the fracture process of the material, whiskers can improve the toughness of the material by absorbing energy and undergoing local plastic deformation. This toughening mechanism mainly stems from the geometric shape and highly oriented structure of the whiskers, which makes the whiskers have extremely high strength and modulus, and their mechanical properties are close to the theoretical values ​​of complete crystals. And they can be evenly distributed in the alloy matrix, effectively preventing the extension of microcracks and enhancing the fracture resistance. In particular, they have advantages in the extension of microcracks, have a good inhibitory effect, and are added to the interface of metal alloys. They have good interfacial compatibility, reflecting the advantages of whisker-reinforced alloy microcracks; the toughening mechanism of whisker fibers, crack deflection and bridging: when cracks extend in composite materials, whiskers can force cracks to deflect, thereby increasing the path length and energy required for crack extension. In addition, whiskers can also cross cracks and form bridges, further hindering the expansion of cracks. Good pull-out effect: When the crack extends to the interface between the whisker and the matrix, the whisker may be pulled out instead of breaking. This pull-out process consumes a lot of energy, thereby improving the toughness of the composite material. It has great advantages in micro-plastic deformation. During the crack propagation process, the matrix around the whisker may undergo micro-plastic deformation, thereby absorbing energy and delaying the expansion of the crack. Excellent heat resistance, high temperature resistance and chemical stability: Inorganic whisker fibers composed entirely of inorganic substances usually have extremely high heat resistance and good chemical stability, and can maintain stable performance in harsh environments. The addition of nano-hybrid whiskers / fiber materials also helps to refine the grains of lightweight high-entropy alloys, thereby increasing the number of grain boundaries, hindering the expansion of dislocations and cracks, and improving the strength and toughness of the alloy. And promote the formation of solid solutions. The hysteresis diffusion effect of nanomaterials also helps to improve the thermal stability of lightweight high-entropy alloys and improve the high temperature resistance of alloys. Since the atomic diffusion rate in nanowhisker materials is slow, the alloy is not prone to adverse effects such as grain coarsening and recrystallization at high temperatures, which is very beneficial to improving the physical properties of lightweight high-entropy alloys.

[0041] At the same time, since the nano-hybrid whisker / fiber material contains active elements that can be internally adsorbed on the grain boundaries to form grain boundary strengthening and grain boundary pinning effects, it can seriously hinder the expansion of dislocations and cracks, and can further improve the strength of the alloy. The addition of nano-hybrid whiskers significantly enhances the mechanical properties of the material. The hysteresis diffusion effect of nanomaterials also helps to improve the thermal stability of lightweight high-entropy alloys. Due to the slow diffusion rate of atoms in nanomaterials, the alloy is not prone to adverse effects such as grain coarsening and recrystallization at high temperatures, which is very beneficial to improving the physical properties of lightweight high-entropy alloys. This can make the structure more uniform, reduce local defects and stress concentration, and thus improve the stability and consistency of the overall performance.

[0042] (3) In the nano hybrid whiskers / fibers added to the lightweight high entropy alloy, the fiber material has high strength and modulus, but its toughness is relatively low. In order to improve the toughness of the fiber material, the compensatory toughness of the whiskers can be increased. When the external force acts on the fiber, macro cracks will be formed in the layer on the fiber surface, resulting in plastic deformation and the generation of bending areas. In this process, the fiber dissipates energy through the shear generated by deformation, thereby improving the toughness of the material. Nanofibers can play a macroscopic skeleton role in composite materials. When the lightweight high entropy alloy is subjected to external force, the nanofibers can effectively transfer the load and improve the strength of the composite material. At the same time, the outstanding advantage of nanofiber materials is that they can also guide the deflection and bridging of the macro cracks of the lightweight high entropy alloy, thereby enhancing the toughness of the composite material. That is, when cracks appear in the alloy, the nanofibers can guide the cracks to deflect, increase the propagation path of the cracks, and improve the fracture resistance; or cross the cracks to form a bridging structure to prevent the further expansion of the cracks, thereby achieving the purpose of compensating the macro cracks of the lightweight high entropy alloy. A good interface bonding can be formed between the nanofibers and the lightweight high entropy alloy matrix. This interface bonding not only helps to effectively transfer the load, but also prevents cracks from extending at the interface, thereby further improving the alloy's fracture resistance. In addition, nanofiber materials generally have a lower density, which allows them to achieve lightweight industrial needs while strengthening and toughening alloys.

[0043] (4) High temperature resistance. High temperature resistant hybrid whisker / fiber-reinforced lightweight high entropy alloy nanocomposites are resistant to high temperatures, which is mainly due to the multi-element structure, excellent thermal stability and corrosion resistance of lightweight high entropy alloys, and the toughening effect of hybrid whiskers / fibers.

[0044] The multi-element structure of lightweight high-entropy alloys will have high mixing entropy. According to the principles of thermodynamics, the increase in mixing entropy will make the system more stable, thereby improving the high-temperature stability of the alloy. The random combination of elements in lightweight high-entropy alloys forms complex local structures and crystal defects, such as lattice distortion and dislocation, which help to improve the thermal stability of the alloy. The lattice distortion effect of lightweight high-entropy alloys makes the diffusion rate of atoms in lightweight high-entropy alloys slower, which enhances the stability of the alloy at high temperatures.

[0045] Lightweight high entropy alloys easily form FCC or BCC dendritic crystal structures with low free enthalpy and contain a small amount of amorphous, microcrystalline and nanophase structures at the grain boundaries, which further improves its corrosion resistance. This corrosion resistance makes the alloy less likely to be oxidized or corroded at high temperatures, thus maintaining high temperature performance.

[0046] By adding hybrid whiskers / fibers to lightweight high-entropy alloys, the toughening effect of hybrid whiskers / fibers can further improve their toughness. These toughening materials can also maintain certain mechanical properties at high temperatures, thereby enhancing the overall high-temperature resistance of the composite material.

[0047] (5) Nano hybrid whisker / fiber materials can enhance the wear resistance and corrosion resistance of lightweight high entropy alloy materials and extend the service life of alloy material components. Nano hybrid whisker / fiber materials have low addition amount and high efficiency. The synergistic effect of whiskers and fibers is reflected in the fact that only a small amount of nano fiber materials and nano whiskers are needed to synthesize to achieve significant performance improvement, which has a high cost performance.

[0048] In a second aspect, the present invention provides a method for preparing a whisker / fiber modified lightweight high entropy alloy nanocomposite material, comprising:

[0049] Step 1: Mixing the powders of the metal components;

[0050] Step 2: Perform the first vacuum arc melting to obtain a lightweight high entropy alloy matrix;

[0051] Step 3: Add nano whisker material and nano fiber material, and perform a second vacuum arc melting to obtain a whisker / fiber modified lightweight high entropy alloy nanocomposite material.

[0052] In some specific embodiments of the present invention, the temperature for melting the high entropy alloy matrix in the first vacuum arc melting is 2500-3000° C., and the melting pressure is 0.05-0.08 Pa.

[0053] In some specific embodiments of the present invention, the temperature for melting the high entropy alloy nanocomposite material in the second vacuum arc melting is 1500-1700° C., and the melting pressure is 0.05-0.08 Pa.

[0054] The preparation method of the lightweight high entropy alloy nanocomposite provided by the present invention adopts vacuum arc melting method for preparation. The vacuum arc melting adopts DC power supply. The arc is more stable in vacuum, not easy to extinguish, and has arc stability, which ensures the continuity and stability of the melting process, and is conducive to the preparation of lightweight high entropy alloy nanocomposite materials with uniform composition and stable performance. The electrodes and crucibles are usually made of metal materials, and the molten metal liquid is protected from contamination by the refractory lining. The smelting is carried out in a closed container, which is pollution-free to the environment and has a good working environment. The smelting is in a vacuum environment, and the smelted metal is protected from oxidation, while promoting degassing and decomposition of metal oxides. It can be efficiently degassed and decomposed, which helps to remove impurities and gases in the alloy and improve the purity and high temperature performance of the alloy. High temperature smelting, vacuum arc melting can provide a high temperature environment to promote uniform mixing of multiple elements. High temperature also helps the full diffusion and reaction of elements in the alloy, thereby preparing a lightweight high entropy alloy nanocomposite material with excellent performance. The vacuum arc melting preparation method has become an effective means to prepare this composite material due to its advantages such as arc stability, pollution-free, efficient degassing and decomposition, and high-temperature melting.

[0055] It should be noted that the existing technology mostly uses plasma sintering process, which will cause the temperature of the metal material to not reach its melting point, and the various elements in the molten metal cannot react completely, thus affecting the density, organizational structure and mechanical properties of the alloy. Vacuum arc furnace melting melts metal materials under high temperature conditions, which is conducive to their complete reaction, and the electrodes and crucibles are usually made of metal materials, which are protected from contamination by the refractory lining by the molten metal, thereby ensuring the purity of the molten metal; it can also process materials of various shapes and sizes, including blocks, rods, etc., with greater flexibility.

[0056] In some specific embodiments of the present invention, the specific steps of the method for preparing a lightweight high entropy alloy nanocomposite material may include:

[0057] Step 1: Ingredients: Select five or more pure metal elements with a purity of not less than 99.95% and mix them according to a certain mass fraction as raw materials, weigh and mix them, and then perform ultrasonic cleaning and dry them in a drying oven. Weigh a certain mass fraction of whiskers and a nanofiber material in a certain proportion to the whisker addition to form a hybrid whisker / fiber material as a performance enhancer, and stir evenly with a glass rod.

[0058] Step 2: Melting lightweight high entropy alloy block: Place the pre-pressed blank into a vacuum arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 2-5 times. Then evacuate the vacuum to 3.0×10 -3Pa, and fill with argon to above 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, smelting is carried out at a furnace temperature of 2700℃. The magnetic stirring function needs to be turned on during the smelting process. Each stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and smelted 3-7 times to ensure uniform smelting. After smelting for 0.5h, a light high-entropy alloy block is obtained.

[0059] Step 3: Melting hybrid whisker / fiber high-strength toughened lightweight high-entropy alloy nanocomposite materials: Place the lightweight high-entropy alloy block melted in the previous step, as well as the whisker and nanofiber materials, into a vacuum arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum washing 2-5 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to above 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting is carried out at a furnace temperature of 1500-1700℃. The magnetic stirring function needs to be turned on during the melting process, and each stirring is 2-10s. Each sample needs to be repeatedly turned over and melted 3-7 times to ensure uniform melting. After melting for 0.5h, a high-strength, toughened, lightweight high-entropy alloy nanocomposite material is obtained.

[0060] Preferably, in steps 2 and 3, the filling with argon gas to a pressure above 0.05Pa is 0.05-0.08Pa.

[0061] In a third aspect, the present invention provides an application of a lightweight high entropy alloy nanocomposite material for use in parts and components in the fields of aviation, aerospace, military, and nuclear industry.

[0062] The preferred embodiments of the present invention are described in detail below to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0063] In the present invention, unless otherwise specified, all reagents used are commercially available products.

[0064] Comparative Example 1

[0065] A lightweight high entropy alloy material is prepared by first selecting five or more pure metal elements of Al, Nb, Ti, V, and Zr with a purity of 99.95% as raw materials according to the formula of AlNbTi 2 V 1.5 20 g of Zr is weighed and mixed. After mixing, it needs to be ultrasonically cleaned and placed in a drying oven for drying.

[0066] Add the dried material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, A1NbTi 2 V 1.5 Zr lightweight high entropy alloy material. After research and testing, A1NbTi 2 V 1.5 The room temperature yield strength of the Zr light high entropy alloy is 1952 MPa and the elongation is 10.7%. The performance parameters are listed in Table 1.

[0067] Example 1

[0068] A high-strength toughened lightweight high-entropy alloy material is prepared by first selecting five pure metal elements of 99.95% pure Al, Nb, Ti, V, and Zr as raw materials according to the formula of AlNbTi 2 V 1.5 20g of Zr is weighed and prepared, and ultrasonic cleaning is performed after preparation, and the mixture is placed in a drying oven for drying. 0.2g of nano-mullite whiskers (length between 1-70μm, diameter between 0.01-0.9μm) and 0.2g of graphene-based carbon fibers (diameter between 0.1-1μm, length between 0.2mm-150mm, and the whiskers and nanofiber materials added in the remaining embodiments are the same size as in Example 1) are used to synthesize hybrid whiskers / fibers as performance enhancers, and stirred and mixed evenly with a glass rod.

[0069] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, A1NbTi 2 V 1.5 Zr lightweight high entropy alloy block.

[0070] The lightweight high entropy alloy block melted in the previous step and 0.2 g of nano-mullite whiskers and 0.2 g of graphene-based carbon fibers after uniform mixing were placed in a vacuum arc melting furnace, and the above steps were repeated to melt at a furnace temperature of 1500-1700 ° C. After melting for 0.5 h, AlNbTi2 V 1.5 Zr high strength toughened lightweight high entropy alloy nanocomposite. After research and testing, adding nano graphene-based carbon fiber / mullite hybrid whisker / fiber A1NbTi 2 V 1.5 The yield strength of the Zr light high entropy alloy at room temperature is 2032 MPa, and the elongation is 15.5%. Compared with comparative example 1, the yield strength of the alloy is increased by 80 MPa, and the elongation is increased by 4.8%. The performance parameters are listed in Table 1.

[0071] Comparative Example 2

[0072] A lightweight high entropy alloy material is prepared by first selecting five pure metal elements of Al, Nb, Ti, V, and Zr with a purity of 99.95% as raw materials, and then 2 NbTi 2 V 2 20 g of Zr is weighed and mixed. After mixing, it needs to be ultrasonically cleaned and placed in a drying oven for drying.

[0073] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted for 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, Al 2 NbTi 2 V 2 Zr lightweight high entropy alloy material. 2 NbTi 2 V 2 The room temperature yield strength of the Zr light high entropy alloy is 2068 MPa and the elongation is 21.5%. The performance parameters are listed in Table 1.

[0074] Example 2

[0075] A high-strength toughened lightweight high-entropy alloy material is prepared by first selecting five pure metal elements of 99.95% pure Al, Nb, Ti, V, and Zr as raw materials. 2 NbTi 2 V 2Weigh 20g of Zr, clean it with ultrasound, and put it in a drying oven for drying. Weigh 0.15g of SiC and 0.2g of S-glass fiber to synthesize hybrid whiskers / fibers as performance enhancers, and mix them evenly with a glass stirring rod.

[0076] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, Al 2 NbTi 2 V 2 Zr lightweight high entropy alloy block.

[0077] The light high entropy alloy block melted in the previous step and 0.15g of SiC and 0.2g of S-glass fiber after mixing were placed in a vacuum arc melting furnace, and the above steps were repeated to melt at a furnace temperature of 1500-1700°C. After melting for 0.5h, Al 2 NbTi 2 V 2 Zr high strength toughened lightweight high entropy alloy nanocomposite. After adding nano SiC / S-glass fiber hybrid whiskers / fibers, Al 2 NbTi 2 V 2 The yield strength of the Zr light high entropy alloy at room temperature is 2143 MPa, and the elongation is 24.5%. Compared with comparative example 2, the yield strength of the alloy is increased by 75 MPa, and the elongation is increased by 3%. The performance parameters are listed in Table 1.

[0078] Comparative Example 3

[0079] A lightweight high entropy alloy material is prepared by first selecting five pure metal elements of Al, Hf, Nb, Ti, and Zr with a purity of 99.95% as raw materials, and then 1.25 20 g of HfNbTiZr is weighed and mixed. After mixing, it needs to be ultrasonically cleaned and placed in a drying oven for drying.

[0080] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, Al 1.25 HfNbTiZr lightweight high entropy alloy material. 1.25 The room temperature yield strength of the HfNbTiZr lightweight high entropy alloy is 1620 MPa and the elongation is 17%. The performance parameters are listed in Table 1.

[0081] Example 3

[0082] A high-strength toughened lightweight high-entropy alloy material is prepared by first selecting five pure metal elements of Al, Hf, Nb, Ti, and Zr with a purity of 99.95% as raw materials, according to Al 1.25 20g of HfNbTiZr was weighed and mixed, and then ultrasonically cleaned and dried in a drying oven. 0.16g of potassium titanate and 0.18g of quartz glass fiber were weighed to synthesize hybrid whiskers / fibers as performance enhancers, and mixed evenly with a glass rod.

[0083] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon for gas washing, and repeat the vacuum washing 3 times. Then evacuate the vacuum to 3.0×10-3Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In an atmosphere of inert gas argon, smelting is carried out at a furnace temperature of 2700℃. The magnetic stirring function needs to be turned on during the smelting process for each stirring, and each stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform smelting. Al is obtained after smelting for 0.5h. 1.25 HfNbTiZr lightweight high entropy alloy block.

[0084] The light high entropy alloy block melted in the previous step and 0.16g of potassium titanate and 0.18g of quartz glass fiber after mixing were placed in a vacuum arc melting furnace, and the above steps were repeated. Al was obtained after melting at a furnace temperature of 1500-1700℃ for 0.5h. 1.25HfNbTiZr high-strength toughened lightweight high-entropy alloy nanocomposite. After research and testing, adding nano potassium titanate / quartz glass fiber hybrid whiskers / fibers to Al 1.25 The yield strength of the HfNbTiZr lightweight high entropy alloy at room temperature is 1776 MPa and the elongation is 19.6%. Compared with comparative example 3, the yield strength of the alloy is increased by 156 MPa and the elongation is increased by 2.6%. The performance parameters are listed in Table 1.

[0085] Comparative Example 4

[0086] A lightweight high entropy alloy material is prepared by first batching, selecting five or more pure metal elements of Al, Hf, Nb, Ti, and Zr with a purity of 99.95% as raw materials, weighing and batching 20g of AlHfNbTiZr, and performing ultrasonic cleaning after batching and drying in a drying oven.

[0087] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In an atmosphere of inert gas argon, smelting is carried out at a furnace temperature of 2700°C. The magnetic stirring function needs to be turned on during the smelting process for each stirring, and each stirring lasts 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform smelting. After 0.5h of smelting, AlHfNbTiZr lightweight high entropy alloy material is obtained. After research and testing, the yield strength of AlHfNbTiZr lightweight high entropy alloy at room temperature is ~1582MPa, and the elongation is ~33%. The performance parameters are listed in Table 1.

[0088] Example 4

[0089] A high-strength toughened lightweight high-entropy alloy material is prepared by first batching, selecting five or more pure metal elements of Al, Hf, Nb, Ti, and Zr with a purity of 99.95% as raw materials, weighing and batching 20g of AlHfNbTiZr, and then performing ultrasonic cleaning and drying in a drying oven. Weigh 0.2g of aluminum borate and 0.2g of alumina fiber to synthesize hybrid whiskers / fibers as performance enhancers, and stir and mix them evenly with a glass rod.

[0090] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process for each stirring, and each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, AlHfNbTiZr light high entropy alloy blocks were obtained.

[0091] The light high entropy alloy block melted in the previous step and 0.2g of aluminum borate and 0.2g of alumina fiber after mixing are placed in a vacuum arc melting furnace, and the above steps are repeated. At a furnace temperature of 1500-1700°C, the AlHfNbTiZr high-strength toughened light high entropy alloy nanocomposite material is obtained after melting for 0.5h. After research and testing, the yield strength of the AlHfNbTiZr light high entropy alloy after adding nano-aluminum borate / alumina fiber hybrid whiskers / fibers is ~1691MPa and the elongation is ~37.5%. Compared with Comparative Example 4, the yield strength of the alloy is increased by ~109MPa and the elongation is increased by ~4.5%. The performance parameters are listed in Table 1.

[0092] Comparative Example 5

[0093] A high-strength toughened lightweight high-entropy alloy material is prepared by first selecting five or more pure metal elements of Co, Fe, Ni, V, and Al with a purity of 99.95% as raw materials according to CoFeNiVAl 0.75 Weigh 20g of ingredients, clean them ultrasonically and put them in a drying oven for drying.

[0094] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, CoFeNiVAl 0.75 Lightweight high entropy alloy material. After research and testing, CoFeNiVAl 0.75 The room temperature yield strength of the lightweight high entropy alloy is 1300 MPa and the elongation is 32%. The performance parameters are listed in Table 1.

[0095] Example 5

[0096] A high-strength toughened lightweight high-entropy alloy material is prepared by first selecting five or more pure metal elements of Co, Fe, Ni, V, and Al with a purity of 99.95% as raw materials according to CoFeNiVAl 0.75 Weigh 20g of ingredients, perform ultrasonic cleaning after mixing, and place in a drying oven for drying. Weigh 0.10g of aluminum oxide and 0.16g of silicon nitride fiber to synthesize hybrid whiskers / fibers as performance enhancers, and stir and mix them evenly with a glass rod.

[0097] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process. Each stirring lasted 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, CoFeNiVAl 0.75 Lightweight high entropy alloy block.

[0098] The light high entropy alloy block melted in the previous step and 0.10g of alumina and 0.16g of silicon nitride fiber after mixing were placed in a vacuum arc melting furnace, and the above steps were repeated. CoFeNiVAl was obtained after melting at a furnace temperature of 1500-1700°C for 0.5h. 0.75 High-strength toughened lightweight high-entropy alloy nanocomposite. After research and testing, CoFeNiVAl after adding nano-alumina / silicon nitride fiber hybrid whiskers / fibers 0.75 The yield strength of the light high entropy alloy at room temperature is 1365 MPa, and the elongation is 39.3%. Compared with comparative example 5, the yield strength of the alloy is increased by 65 MPa, and the elongation is increased by 7.3%. The performance parameters are listed in Table 1.

[0099] Comparative Example 6

[0100] A lightweight high entropy alloy material is prepared by first batching, selecting five or more pure metal elements of Co, Fe, Ni, V, and Al with a purity of 99.95% as raw materials, weighing and batching 20g of CoFeNiVAl, and performing ultrasonic cleaning after batching and drying in a drying oven.

[0101] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In an atmosphere of inert gas argon, smelting is carried out at a furnace temperature of 2700°C. The magnetic stirring function needs to be turned on during the smelting process for each stirring, and each stirring lasts 2-10s. Each sample needs to be repeatedly turned over and smelted 6 times to ensure uniform smelting. After 0.5h of smelting, CoFeNiVAl lightweight high entropy alloy material is obtained. After research and testing, the yield strength of CoFeNiVAl lightweight high entropy alloy at room temperature is ~1150MPa, and the elongation is ~28%. The performance parameters are listed in Table 1.

[0102] Example 6

[0103] A high-strength toughened lightweight high-entropy alloy material is prepared by first batching, selecting five or more pure metal elements of Co, Fe, Ni, V, and Al with a purity of 99.95% as raw materials, weighing 20g of the ingredients according to CoFeNiVAl, and then performing ultrasonic cleaning and drying in a drying oven. Weigh 0.05g of zinc oxide and 0.2g of M-glass fiber to synthesize hybrid whiskers / fibers as performance enhancers, and stir and mix them evenly with a glass rod.

[0104] Add the dried metal material into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and filled with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. In the atmosphere of inert gas argon, the melting was carried out at a furnace temperature of 2700℃. The magnetic stirring function was turned on during the melting process for each stirring, and each stirring lasted for 2-10s. Each sample needed to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for 0.5h, a CoFeNiVAl light high entropy alloy block was obtained.

[0105] The light high entropy alloy block melted in the previous step and 0.05g zinc oxide and 0.2g M-glass fiber after mixing are placed in a vacuum arc melting furnace, and the above steps are repeated. At a furnace temperature of 1500-1700°C, the CoFeNiVAl high-strength toughened light high entropy alloy nanocomposite material is obtained after melting for 0.5h. After research and testing, the yield strength of the CoFeNiVAl light high entropy alloy after adding nano zinc oxide / M-glass fiber hybrid whiskers / fibers is ~1235MPa, and the elongation is ~33.6%. Compared with comparative example 6, the yield strength of the alloy is increased by ~85MPa and the elongation is increased by ~5.6%. The performance parameters are listed in Table 1.

[0106] Example 7

[0107] This embodiment is basically the same as the embodiment 1, except that the whiskers are calcium carbonate whiskers and the added amount of calcium carbonate whiskers is 0.98%wt.

[0108] Example 8

[0109] This embodiment is basically the same as the embodiment 1, except that the fiber type is basalt fiber, and the mass percentage of the basalt fiber is 0.98%wt.

[0110] Example 9

[0111] This embodiment is substantially the same as the embodiment 1, except that in the composite material, the addition amount of the hybrid whiskers / fibers is: mullite whiskers (1.5% wt) + graphene-based carbon fibers (0.46% wt).

[0112] Example 10

[0113] This embodiment is substantially the same as the embodiment 1, except that in the composite material, the addition amount of the hybrid whiskers / fibers is: mullite whiskers (0.46% wt) + graphene-based carbon fibers (1.5% wt).

[0114] Comparative Example 7

[0115] This comparative example is substantially the same as Example 1, except that the composite material does not include graphene-based carbon fibers, and the mass percentage of mullite whiskers is 1.96%wt.

[0116] Comparative Example 8

[0117] This comparative example is substantially the same as Example 1, except that the composite material does not include mullite whiskers, and the mass percentage of graphene-based carbon fibers is 1.96%wt.

[0118] Table 1. Performance analysis of materials prepared in comparative examples and examples

[0119]

[0120]

[0121]

[0122] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A whisker / fiber modified lightweight high entropy alloy nanocomposite material, characterized in that: The composite material comprises a light high entropy alloy matrix and a hybrid whisker / fiber material. Based on the total weight of the composite material, the mass percentage of the hybrid whisker / fiber material is 0.01wt.%-8.00wt.%.

2. The material according to claim 1, characterized in that The hybrid whisker / fiber material comprises a whisker material and a fiber material, and the mass ratio of the whisker material to the fiber material is (0.01-1):

1.

3. The material according to claim 1, characterized in that The whisker material has a length of 1-70 μm and a diameter of 0.01-0.9 μm; And / or, the fiber material has a diameter of 0.1-1 μm and a length of 0.2 mm-150 mm.

4. The material according to claim 2, characterized in that The material of the whisker material includes at least one of SiC, mullite, potassium titanate, aluminum borate, calcium sulfate, calcium carbonate, aluminum oxide, and zinc oxide; And / or, the fiber material is made of at least one of graphene-based carbon fiber, S-glass fiber, M-glass fiber, basalt fiber, quartz glass fiber, alumina fiber, and silicon nitride fiber.

5. The material according to any one of claims 1 to 4, characterized in that The lightweight high-entropy alloy matrix includes metal components, and the metal components include at least five of Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Hf, Ta, and W.

6. The material according to claim 5, characterized in that The metal components include a first metal component, a second metal component, a third metal component, a fourth metal component, and a fifth metal component, which are different from each other. Taking the total atomic percentage of the lightweight high entropy alloy matrix as 100%, the atomic percentages of the first metal component, the second metal component, the third metal component, the fourth metal component, and the fifth metal component are the same or different, and are each independently 5 to 35 at.%.

7. A method for preparing the whisker / fiber modified lightweight high entropy alloy nanocomposite material according to any one of claims 1 to 6, characterized in that: include: A mixture including metal component powders is obtained, subjected to a first vacuum arc melting, and then whisker materials and fiber materials are added and subjected to a second vacuum arc melting to obtain the whisker / fiber modified lightweight high entropy alloy nanocomposite material.

8. The preparation method according to claim 7, characterized in that: The temperature of the first vacuum arc melting is 2500-3000° C., and / or the pressure of the first vacuum arc melting is 0.05-0.08 Pa.

9. The preparation method according to claim 7 or 8, characterized in that: The temperature of the second vacuum arc melting is 1500-1700° C., and / or the pressure of the second vacuum arc melting is 0.05-0.08 Pa.

10. An application of a lightweight high entropy alloy nanocomposite material according to any one of claims 1 to 6 or a lightweight high entropy alloy nanocomposite material prepared by the preparation method according to any one of claims 7 to 9, characterized in that: The lightweight high entropy alloy nanocomposite material is used for parts in the fields of aerospace, medicine, energy, military and transportation.